Interference in Combined Cochlear Implant and Hearing Aid Use: A Scoping Review. - Noel, Augustina; Jaisinghani, Priyanka; Balan, Jithin (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Advancements in cochlear implant (CI) and hearing aid (HA) technology enabled the combining of acoustic and electric stimulation for bimodal hearing and electro-acoustic stimulation (EAS) among listeners with hearing loss. While some users experience benefits such as enhanced speech or music perception and improved localization, others face interference between CI and HA, potentially leading to HA discontinuation. Our study aims to explore the underlying causes of interference, map existing evidence, and identify potential research gaps. The insights gained on interference will help foresee and mitigate such scenarios, improving speech and music perception in bimodal and EAS users. Method: This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews guidelines, and it was registered on protocols.io (access online at dx.doi.org/10.17504/protocols.io.dm6gp37xdvzp/v2). Inclusion criteria were peer-reviewed articles written in English and published between 2000 and May 2024, and articles reported adverse performance outcomes with combined CI and HA use in adults or children compared to CI or HA alone. Relevant articles were searched using specific key words and Boolean operators across multiple databases. Results: The final scoping review included 15 articles published across 13 scientific journals. These articles originated from nine countries and underwent narrative analysis to extract insights on interference in combined CI and HA use. Conclusions: The study offers valuable insights into the prevalence, causes, and assessment of interference in the combined use of CI and HA. Our review suggests that bimodal interference is individualized or listener-specific, with various factors affecting the utility of bimodal and EAS. Thus, a mixed-methods approach should be implemented in the future to gain a more comprehensive understanding of interference. Customized strategies can also be explored and applied to reduce interference through HA programming, CI mapping, counseling, and training to enhance the benefits for bimodal and EAS users.